KIPRAH NU (NAHDATUL ULAMA) DALAM PENDIDIKAN INDONESIA - Muhammad Hafid Abdi; Fatimah Depi Susanti Harahap; Rika Mutiara Shandi; Nur Aliya (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
Nahdlatul Ulama (NU) has an important role in the world of education as one of the largest Islamic organizations in Indonesia. Since its founding in 1926, NU has been committed to developing education based on moderate Islamic teachings and integrating religious knowledge with popular knowledge. The purpose of this article is to analyze NU's efforts in the field of education, especially through Islamic boarding schools, madrasah, and other educational institutions. By analyzing NU's history and contributions, it is hoped that we can better understand its role in creating a generation that is intelligent, moral, and competitive in the global world.